Birds from cerradão woodland, an overlooked forest of the Cerrado region, Brazil - Cavarzere, Vagner; Moraes, Gabriel Parmezani; Dalbeto, Andreli Cristina; Maciel, Fernanda de Góes; Donatelli, Reginaldo José (Papéis Avulsos de Zoologia, 2011)
The Cerrado region still receives relatively little ornithological attention, although it is regarded as the only tropical savanna in the world considered to be a biodiversity hotspot. Cerradão is one of the least known and most deforested Cerrado physiognomies and few recent bird surveys have been conducted in these forests. In order to rescue bird records and complement the few existing inventories of this under-studied forest type in the state of São Paulo, we looked for published papers on birds of cerradão. Additionally we surveyed birds at a 314-ha cerradão remnant located in central São Paulo, Brazil, from September 2005-December 2006 using unlimited distance transect counts. Out of 95 investigations involving cerradão bird studies, only 17 (18%) investigations teased apart bird species recorded inside cerradão from those recorded in other physiognomies of Cerrado. Except for one study, no research found more than 64 species in this type of forest, a result shared within many regions from Brazil and Bolivia. Differences in species richness do not seem be related with levels of disturbance of landscape or fragment size. Considering all species recorded in cerradão in Brazil and Bolivia, a compilation of data accumulated 250 species in 36 families and 15 orders. In recent surveys at central São Paulo, we recorded 48 species in 20 families, including the Pale-bellied Tyrant-Manakin Neopelma pallescens, threatened in São Paulo, and the Helmeted Manakin Antilophia galeata, near threatened in the state and endemic to the Cerrado region. Among the most abundant species inside this fragment, none was considered to be neither threatened nor endemic.